Determinants of Inflation Targeting: A Survey of Empirical Literature - Goran Petrevski (ZBW - Leibniz Information Centre for Economics, 2023)
This paper surveys the empirical literature of dealing with the choice of inflation targeting (IT). Specifically, the paper focuses on the main institutional, macroeconomic, and technical determinants affecting the adoption of IT. The main findings from our review are the following: there is strong empirical evidence that larger and more developed countries are more likely to adopt the IT regime; similarly, the introduction of IT regime is conditional on previous disinflation, greater exchange rate flexibility, central bank independence, and higher level of financial development; however, the literature suggests that the link between various macroeconomic and institutional determinants and the likelihood of adopting IT may be rather weak, i.e., they are not to be viewed either as strict necessary or sufficient conditions.
Keywords: E52; E58; 330; inflation targeting; monetary policy; emerging markets economies